Molecular and phenotypic characteristics of RSV infections in infants during two nirsevimab randomized clinical trials - Madhi, Shabir A.; Ahani, Bahar; Tuffy, Kevin M.; Aksyuk, Anastasia A.; Wilkins, Deidre; Abram, Michael E.; Dagan, Ron; Domachowske, Joseph B.; Guest, Johnathan D.; Ji, Hong; Kushnir, Anna; Leach, Amanda; et al. (Nature Research, 2023)
Nirsevimab is a monoclonal antibody that binds to the respiratory syncytial virus (RSV) fusion protein. During the Phase 2b (NCT02878330) and MELODY (NCT03979313) clinical trials, infants received one dose of nirsevimab or placebo before their first RSV season. In this pre-specified analysis, isolates from RSV infections were subtyped, sequenced and analyzed for nirsevimab binding site substitutions; subsequently, recombinant RSVs were engineered for microneutralization susceptibility testing. Here we show that the frequency of infections caused by subtypes A and B is similar across and within the two trials. In addition, RSV A had one and RSV B had 10 fusion protein substitutions occurring at >5% frequency. Notably, RSV B binding site substitutions were rare, except for the highly prevalent I206M:Q209R, which increases nirsevimab susceptibility; RSV B isolates from two participants had binding site substitutions that reduce nirsevimab susceptibility. Overall, >99% of isolates from the Phase 2b and MELODY trials retained susceptibility to nirsevimab.
Keywords: Antibodies; Biological therapy; Paediatric research; Viral infection; SDG-3: Good health and well-being